Estimation of white grub damage (Coleoptera : Scarabaeoidea) in cork oak (Quercus suber L.) regeneration parcels of the Mamora forest (Morocco) and search for biological control using sex pheromones. - Ghaioule, Driss; Lumaret, Jean-Pierre; Rochat, Didier; Maatouf, Noureddine; Niogret, Jerome (ANNALES DE LA SOCIETE ENTOMOLOGIQUE DE FRANCE, 2007)
During the last decades, the cork oak restoration in the Mamora forest (Morocco) was faced with massive root attacks of seedling plantations by white grubs (Coleoptera: Scarabaeoidea). In most cases, the success of the restoration reached only 12%. Sphodroxia maroccana Ley (Melolonthidae) can be considered as the main pest in the restoration parcels. Some traits of the biology of this species are specified, despite shortcomings in the knowledge of the precise period of male emergence with regard to females, the longevity of adults and the sex-ratio. Summer drought, a season without white grub activity, is another main cause of mortality of young plantations. During the first year after plantation in experimental parcels, the cumulated mortality due to these two factors ranged between 41 and 68% according to the blocks in the parcels. The mortality associated with S. maroccana larvae ranged between 24 and 43%, with a distribution of infestation depending on density of young plants. Solid phase micro-extraction used to sample volatiles from the headspace of S. maroccana females allowed to isolate resorcinol (1,3-benzenediol) as presumed female sex pheromone. The role of this molecule has to be demonstrated.
The following values have no corresponding Zotero field: pub-location: 45 RUE BUFFON, 75005 PARIS, FRANCE publisher: SOC ENTOMOLOGIQUE FRANCE
Keywords: 1-3-benzenediol; biological control; Cork oak; damage; Morocco; pheromone; resorcinol; Restoration; Scarabaeoidea; white grubs